Testosterone and cardiac mass and function in men with type 1 diabetes in the Epidemiology of Diabetes Interventions and Complications Study (EDIC). (25th January 2016) - Kim, Catherine; Bebu, Ionut; Braffett, Barbara; Cleary, Patricia A.; Arends, Valerie; Steffes, Michael; Wessells, Hunter; Orchard, Trevor; Sarma, Aruna V.; ,
Summary: Objective: Low testosterone concentrations have been reported to be associated with increased risk of congestive heart failure, but the mechanisms are unclear. Our objective was to examine the relationship between endogenous testosterone and measures of cardiac mass and function among men with type 1 diabetes. Design: Secondary analysis of a prospective observational study. Participants: Men ( n = 508) in the Epidemiology of Diabetes Interventions and Complications (EDIC) study, the observational follow‐up of the Diabetes Control and Complications Trial (DCCT). Measurements: Testosterone assessed by liquid chromatography mass spectrometry at EDIC year 10 and cardiac magnetic resonance imaging (CMR) measures at EDIC years 14/15. Linear regression models were used to assess the relationship between testosterone, sex hormone binding globulin (SHBG) and left ventricular (LV) mass, volume, ejection fraction and cardiac index before and after adjustment for age, randomization arm, alcohol and cigarette use, macroalbuminuria, haemoglobin A1c, insulin dose, body mass index, lipids, blood pressure, use of antihypertensive medications and microvascular complications. Results: In fully adjusted models, total testosterone concentrations were significantly associated with LV mass ( P = 0·014), end‐diastolic volume ( P = 0·002), end‐systolic volume ( P = 0·012) and stroke volume ( P = 0·022), but not measures of LV function after adjustment for cardiac risk factors. Bioavailable testosterone was associated with LV mass, but not volume or function, while SHBG was associated with volume, but not mass or function. Conclusions: Among men with type 1 diabetes, higher total testosterone was associated with higher LV mass and volume, but not with function. The clinical significance of this association remains to be established.